A novel glass-fiber-aided cold-press method for fabrication of n-type Ag2Te nanowires thermoelectric film on flexible copy-paper substrate. Issue 47 (20th November 2017) - Gao, Jie; Miao, Lei; Liu, Chengyan; Wang, Xiaoyang; Peng, Ying; Wei, Xingyu; Zhou, Jianhua; Chen, Yu; Hashimoto, Ryo; Asaka, Toru; Koumoto, Kunihito
Abstract : A novel glass-fiber aided cold-press method for achieving n-type Ag2 Te nanowires film on a flexible copy paper substrate. Abstract : Being light, cheap, breathable and foldable, paper is emerging as a new type of substrate for flexible thermoelectric films. Several techniques including soaking and magnetron sputtering have been developed to coat inorganic semiconductors onto paper substrate, but the flexibility and thermoelectric performance of the resulting films are still far from satisfactory. This work implements a novel glass-fiber-aided cold-press method for achieving flexible n-type Ag2 Te nanowire (NW) films on copy-paper substrate. A greatly enhanced electrical conductivity has been realized in Ag2 Te NWs film due to the disappearance of grain boundaries under compression to 30 MPa. As a consequence, the largest power factor (PF) value of up to 192 μW (mK 2 ) −1 at 195 °C surpasses the performance of paper based thermoelectric films reported previously. Moreover, the PF value only decreases by 20% after 500 bending cycles, suggesting the good flexibility of the copy-paper supported Ag2 Te NWs films. A thermoelectric module containing 10 pieces of series-connected Ag2 Te films is fabricated using this glass-fiber-aided cold-press method. With Δ T increasing from 20 K to 80 K, the open-circuit voltage of module continually increases from about 11 mV to 60 mV. This measurement of open-circuit voltage has been repeated 10 times to confirm the stability of paper-supported Ag2 Te thermoelectric module. The glass-fiber-aided cold-press method in this study provides an effective access to high-performance, flexible and solvent-processable inorganic thermoelectric films on copy-paper substrate.